The influence of testosterone level in male rats on gastrotoxicity of non-steroidal anti-inflammatory drugs (NSAIDs) - Voloshchuk N.I. (Medičnì Perspektivi)
In experiments on male rats the influence of different degree of saturation of rats organism with testosterone on gastrotoxicity of diclophenac-sodium, nomesulide and celecoxib was investigated. It was shown that testosterone promoted increase of damaging action of NSAIDs on the stomach. After gonadectomy the multiplicity and severity of gastric lesion were by 2,5 less than in intact rats. Replacement therapy with testosterone increased ulcerogenic action of diclophenac by 2,9 times in comparison with rats after gonadectomy. Excessive introduction of testosterone promoted more intensive gastrotoxicity in comparison with intact rats. Investigation of biochemical markers of protective barriers of gastric mucosa in male rats has shown that testosterone is the factor which decreases stomach mucosal defense. Gonadectomy of male rats increases production of glycosaminoglycanes, nitrite/nitrates (by 17,7%), and SOD activity (by 16,9%) and at the same time decreases MDA level (by 17,3%). Substitutive and excessive introduction of testosterone caused opposite effect. Introduction of diclophenac sodium during 7 days resulted in macroscopic changes in gastric mucosa and was accompanied with decreasing of glycosaminoglycanes, nitrite/nitrates and SOD activity and increasing of MDA level. These changes directly correlated with the level of saturation with testosterone in male organism. Thereby accounting level of androgen saturation in organism of male rats gives possibility to correct the dose of NSAIDs and opens new perspectives for selection of optimal drug-correctors of NSAIDs gastrotoxicity.